Resilience-based interventions for parents of children with cancer: a systematic review - Sinaga, Sumiati; Abdul Mulud, Zamzaliza (Intelektual Pustaka Media Utama, 2025)
Childhood cancer diagnosis and treatment can have a negative impact, not only on the child but also on the parents. the study aims to systematically summarize the effectiveness of resilience-based interventions in parents of children with cancer. A systematic review was conducted on eight studies that met the eligibility criteria. Article searches were conducted using the PICO framework through six databases PubMed, Scopus, ScienceDirect, Proquest, WoS, and Clinical Key. The literature search followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Article searches were limited to publication years ranging from 2019 to 2023 using the keywords